AN ANALYSIS OF INTERRUPTION IN SEMINAR SETTING - Jakob, Juvrianto Chrissunday; Pertiwi, Sri Ananda (Research And Innovation In Language Learning (RILL), 2019)
Interruption is a phenomenon when one person takes the turn while another is already talking.  Most of the time, phenomena of interruption has been considered as disrespectful act or kind of rude. Contrast, Interruption could be supportive and cooperative act. This study aimed at describing what type of interruption is and reason of doing interruption made by English lectures and students in proposal seminar. This research used qualitative method which the data of interruption are taken from participants in three different proposal seminar conducted by graduate students of UNM by using recording technique. The results showed that types of interruption appeared in seminar are simple interruption, silent interruption, and butting interruption. Otherwise, the reasons of interruption which appears are seeking clarification, correcting, disagreeing, giving clarification, doubting and giving explanation. This is due to the fact that interruptions in this seminar were not violation.